PENGGUNAAN MEDIA PEMBELAJARAN AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS DI KELAS IV SD NEGERI SYOTA - Sairtory, Elsi Nonsi; Septory, Jekriel (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low learning outcomes of students in IPAS subjects in grade IV of Syota State Elementary School due to teacher-centred learning and a lack of learning media. This study aims to improve student learning outcomes on the subject of ethnic, national, and cultural diversity in Indonesia through the use of audio-visual media. The research method used was Classroom Action Research, which was carried out in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. Data were collected through observation, learning outcome tests, interviews, and documentation, then analysed qualitatively and quantitatively. The results showed that the use of audio-visual media was able to increase student engagement and understanding during the learning process. The percentage of learning completeness increased from 40% in cycle I to 100% in cycle II, and all students exceeded the minimum passing grade. Thus, it can be concluded that audio-visual media is effective in improving the learning outcomes of Grade IV students at Syota State Elementary School and is suitable for use as an alternative learning medium in elementary schools